THE RELATIONSHIP SEXUAL BEHAVIOR ADOLESCENCE - Nay Lufar (Poltekkes 'Aisyiyah Banten, 2022)
Background: Sexual behavior in adolescents is very dependent on the sexual knowledge possessed by the child. Sexual behavior is behavior related to reproductive functions or that stimulates sensation in receptors located on or around the reproductive organs or erogenous areas. Adolescence is a period of development in all respects, so that being unstable or easily influenced is a characteristic of adolescents themselves. The rapid development of social media among teenagers as a communication tool that is easy to use by anyone and can be accessed anywhere has created a major phenomenon in the flow of information, not only that, the increasingly rapid growth of social media has caused various effects for the youth themselves, both physical and psychological effects. positive and negative effects. The purpose of this study was to determine the relationship between the use of social media with premarital sexual knowledge in adolescents at SMAN 1 Kramatwatu. The research method used is quantitative, namely the cross sectional analytical survey method. The results of the analysis show that there is a relationship between the use of social media, the role of parents, the role of teachers and the role of peers with premarital sexual knowledge in adolescents at SMAN 1 Kramatwatu with a p-value <0.05. Keywords: Social Media, Premarital Sexual Knowledge, Teenagers